IoT Enabled Smart Hospital Management System for Covid-19 Patients - et. al., Abhishek Singh, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The hospital management system in rural areas lacks the proper treatment due to demand of efficient doctors and health care persons. Also, in this situation of COVID-19 pandemic, common people are facing problems in health check up facilities. As per the latest report India has the doctor to patient ratio which is much below the recommended by the WHO. As per WHO guidelines, there should be one doctor for every 1000 patients, in health care environments. India has a ratio of 1:1445 as per the latest records. Also, as per rules PPE kits are essential for the health care persons to handle the corona patients. India still faces the shortage of these PPE kits, which are needed to be manufactured by the Indian ordnance factories. To address this issue, an IoT based system has been developed, which could aid in overcoming the doctor shortage in health care environments. The IoT system designed is a wearable device to be weared by the patient, which could monitor the pulse rate, temperature and SpO2 levels of the concerned patient. The data can be sent to the cloud to be stored on any IoT server like Thingspeak or any other servers like Adafruit.